Increasing Doxycycline Hyclate Photostability by Complexation with β-Cyclodextrin - Kogawa, Ana Carolina (2014)
Doxycycline hyclate (DOX) is a highly photosensitive drug, a feature that limits the stability of the corresponding dosage forms. The main objectives of this work were the preparation and characterization of an inclusion complex of DOX with β-cyclodextrin (βCD) and to investigate if this approach could improve the photostability of the drug. Guest-host interactions were investigated using nuclear magnetic resonance, which were afterwards combined with molecular modeling methods to study the complex formation and its three-dimensional structure was proposed. A freeze-drying method was applied to obtain the complex in the solid state, which was further confirmed by thermal and spectroscopic techniques. To evaluate the complexation effect on DOX integrity, the photostability of the inclusion complex was studied, with a significant decrease in the photodegradation of DOX being found in aqueous solution upon complexation. Finally, the photoprotection produced by the complexation was evaluated by means of an antimicrobial assay. Overall, the presented results suggest that the formulation of DOX complexed with βCD constitutes an interesting approach for the preparation of pharmaceutical dosage forms of DOX with enhanced stability properties.